2022
DOI: 10.1037/abn0000765
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effects of schizophrenia genetic risk on cortical thickness and cortical surface area: Evaluating evidence for neurodevelopmental and neurodegenerative models of schizophrenia.

Abstract: Risk for schizophrenia peaks during early adulthood, a critical period for brain development. Although several influential theoretical models have been proposed for the developmental relationship between brain pathology and clinical onset, to our knowledge, no study has directly evaluated the predictions of these models for schizophrenia developmental genetic effects on brain structure. To address this question, we introduce a framework to estimate the effects of schizophrenia genetic variation on brain struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…In our previous study, we observed that CT and SA showed significant neurogenetic effects in the later phases of illness but not in the early phases. 54 We also observed that the genetic effects shared between deficits in general cognition and schizophrenia were nonsignificant in the early phases of the illness than during the later stages. 55 These data suggest that gene expression differences may impact CT changes in patients with longer duration of illness than those with short duration of illness.…”
Section: Discussionmentioning
confidence: 56%
“…In our previous study, we observed that CT and SA showed significant neurogenetic effects in the later phases of illness but not in the early phases. 54 We also observed that the genetic effects shared between deficits in general cognition and schizophrenia were nonsignificant in the early phases of the illness than during the later stages. 55 These data suggest that gene expression differences may impact CT changes in patients with longer duration of illness than those with short duration of illness.…”
Section: Discussionmentioning
confidence: 56%
“…Particularly, the ENIGMA Relatives Working Group reported a reduction in mean cortical thickness (CT) in SCZ-RELs compared to HCs [92]. Additionally, a study conducted on 200 SCZ-RELs (aged 12-85 years) and 276 unrelated controls suggested early neurodevelopmental effects of the SCZ genetic risk for frontal and insular SA, late neurodevelopmental effects for overall cortical SA, and frontal, parietal, and occipital SA, and possible neurodegenerative effects for temporal CT and parietal SA [97]. Interestingly, a reduction in frontal and temporal SA in SCZ-RELs was correlated with subjective cognitive dysfunction and predisposition to hallucinations [98].…”
Section: Structural Sudiesmentioning
confidence: 99%